Studying the effect of low doses of gamma and beta irradiations on graphene oxide samples. (August 2020) - Yasein, M.; Eissa, M.F.; El-Fayoumi, M.A.K.; Abood, Ahmed A.; Badawi, Emad A.; Aly, Arafa H.
Abstract: Graphene oxide (GO) sheets have many applications such as biomedical, solar cells, batteries, supercapacitors and biosensors. The product of GO sheets was irradiated in the air by gamma-rays ( 60 Co source) and beta particles ( 90 Sr source). Positron Annihilation Doppler-Broadening technique was used to study the effect of radiation on GO samples. The interlayer spacing (d-spacing) of GO layers was measured by X-ray diffraction before and after irradiation processes. The d-spacing of GO was decreased after beta particles and gamma-ray irradiation. Raman spectroscopy measurements were performed on irradiated and non-irradiated GO samples. The measured data showed that the disorder parameter defect ratio for the gamma-ray irradiation was decreased. Fourier transform infrared spectra were applied to obtain information on the functional groups attached to irradiated and non-irradiated GO samples. The results obtained a reduction in oxygen-functional groups of the GO samples as well as the optical absorption spectra of all samples were measured. Highlights: GO samples were irradiated by beta particle and gamma-ray radiations doses. The characterization processes were performed using PADBS, FT-IR, UV-Vis, XRD, and Raman Spectroscopy. Significant changes in the chemical structure of irradiated GO samples. Significant effects of background radiation on GO-based on components in the long-term.